Do Executive Functions Predict Binge-Drinking Patterns? Evidence from a Longitudinal Study in Young Adulthood - Bø, Ragnhild; Billieux, Joël; Gjerde, Line C.; Eilertsen, Espen M.; Landrø, Nils I. (Frontiers in Psychology, 2017)
Background: Impairments in executive functions (EFs) are related to binge drinking in young adulthood, but research on how EFs influence future binge drinking is lacking. The aim of the current report is therefore to investigate the association between various EFs and later severity of, and change in, binge drinking over a prolonged period during young adulthood. Methods: At baseline, 121 students reported on their alcohol habits (the Alcohol use disorder identification test; Alcohol use questionnaire). Concurrently, EFs (working memory, reversal, set-shifting, response inhibition, response monitoring and decision-making (with ambiguity and implicit risk)) were assessed. Eighteen months later, information on alcohol habits for 103 of the participants were gathered. Data were analyzed by means of multilevel regression modeling. Results: Future severity of binge drinking was uniquely predicted by performance on the Information sampling task, assessing risky decision-making (β = -1.86, 95% CI: -3.69, -0.04). None of the study variables predicted severity or change in binge drinking. Conclusion: Future severity of binge was associated with making risky decisions in the prospect for gain, suggesting reward hypersensitivity. Future studies should aim at clarifying whether there is a causal association between decision-making style and binge drinking. Performance on all executive tasks was unrelated to change in binge drinking patterns; however, the finding was limited by overall small changes, and needs to be confirmed with longer follow-up periods.